IMPLEMENTATION OF THE ORGANIZING FUNCTION AND SUPERVISION BY THE HEAD OF THE ROOM AT THE MOTHER AND CHILDREN'S HOSPITAL LOVE OF THE CIPUTAT STUDY PHENOMENOLOGY - Maria Delviana Nurdiani; Blacius Dedi; Wilhemus Hary Susilo (Jurnal Ilmiah Perawat Manado (Juiperdo), 2019)
Background: The implementation of the organizing and supervision function by the Head of the room in several medical wards has not been optimal yet. The head of the room claimed that 90% of staff have never been given nursing care audits and 80% of staff have never been given nursing supervision. There are 90% nurses and midwives who do not know the structure and organization of nursing, 60% nurses and midwives do not know their job description and responsibility, and 62,5% of nurses and midwives do not know about nursing care methods which are applied in providing services (Residency Results 2018). Aims: This study to know-how experience of the head nurse to implementation organizing and supervision function. Methods: The method of research is qualitative which is used descriptive phenomenology design and the data analysis method is using phenomenological Colaizzi (Polit and Beck, 2012). Result : The research was supported by 6 participants, there are 9 main parts: providing guidance to nursing staff, making priority schedules for operations implementation, resolving existing problems with situational and flexible management, self-evaluation and jointly finding solutions in organizing staff, ability to carry out the duties as ahead of the room, cooperation with nursing managers in order to improve service,. SPO used in the room can facilitate the head of space and staff in carrying out actions. Conclusion: there is a new job desk socialization time, HR Requests that have not been fulfilled yet.